Analysis of particulate distributed across Fukushima Prefecture: Attributing provenance to the 2011 Fukushima Daiichi Nuclear Power Plant accident or an alternate emission source. (1st September 2019) - Martin, Peter George; Davies-Milner, Merrick; Nicholson, John; Richards, David; Yamashiki, Yosuke; Scott, Thomas
Abstract: Over eight years have now passed since the chain of events that occurred at Japan's Fukushima Daiichi Nuclear Power Plant (FDNPP) and despite this, considerable research effort continues to be expended – yielding results pertinent to understanding the conditions behind the numerous radioactivity release events. As well as investment in this extensive scientific research, great effort is also being directed to the large-scale remediation of the radiologically-affected area and is set to continue for the foreseeable future. Central to this has been the study of the highly-volatile and high-yield fission products of cesium ( 134 Cs and 137 Cs) and iodine ( 129 I and 131 I), which were together dispersed at considerable total activities as a consequence of the accident. In contrast to investigating the distribution (and state) of these high-activity fission products, this study examined fragments of transition metals, rare earth elements and actinides found adhered to a diverse range of organic samples collected from localities across the radiologically contaminated Fukushima Prefecture. As well as varying enormously in their elemental composition, the entrapped particulates comprised a wide size range (150 nm to >10 μm). For particulate of certain compositions (including Ag, Ce, Sm, and Au), a correlation was observed between their size and the distance at which they were encountered from the FDNPP. While a trend was apparent for these and several other composition particles, other materials (including Zr, Pb, Sn, and Ba) could not be described by such a strongly-negative linear trend. Although a Fukushima provenance could be apportioned to a component of the material, an alternate source is necessary to account for a significant inventory of the particulate material. While contrasting provenances may exist, both the size and composition of this particulate could represent potentially significant health implications for exposed populations. Highlights: Particulate material from the area surrounding the FDNPP analysed. Correlation in size of certain composition fragments with distance from the FDNPP. Potential attribution to both the FDNPP releases and other anthropogenic sources. Environmental legacy of particulate contamination.